Influence of N, P, and Fe availability on Braarudosphaera bigelowii, Trichodesmium, Crocosphaera, and noncyanobacterial diazotrophs: a review - Cao, Wenhui; Yang, Qunhui; Ji, Fuwu; Liu, Cheng (Frontiers in Marine Science, 2024)
Marine biological nitrogen fixation (BNF) is crucial for introducing “new nitrogen” into the oceans. Over the past 30 years, numerous laboratory and on-board culture experiments have been conducted studying the effects of nutrients such as total dissolved nitrogen (TDN), total dissolved phosphorus (TDP), and dissolved iron (DFe) on marine diazotrophs such as Braarudosphaera bigelowii (B. bigelowii), Trichodesmium, Crocosphaera and noncyanobacterial diazotrophs (NCDs). Most studies concluded that elevated dissolved inorganic nitrogen levels inhibit nitrogen fixation in Trichodesmium, promote its growth, and have minimal effect on B. bigelowii. The impact on NCDs is unclear. Moreover, elevated dissolved inorganic phosphorus (DIP) levels can promote individual growth, population growth, and nitrogen fixation in most diazotrophs in P-limited marine environments. Dissolved organic phosphorus is a potential phosphorous source for diazotrophs in low-DIP environments. Elevated DFe can promote population growth and nitrogen fixation in diazotrophs in Fe-limited marine environments. At present, most diazotrophs have yet to achieve pure culture. Moreover, the effect of nutrients on diazotrophs is mainly limited to the study of a single nutrient, which cannot accurately reflect the actual Marine environment where diazotrophs live. As a result, our understanding of the effect of nutrients on diazotrophs is still insufficient. Future research focusing on the issues above and the development of innovative technologies and methodologies to investigate the impact of marine BNF is highly recommended, which will allow for a more precise assessment of the impact of marine BNF on global primary productivity while providing a scientific foundation for rational evaluation of ocean CO2 uptake and emissions.